The Violation of Cooperative Principles in The Dialogue Among The Characters of David Baldacci’s The Escape (2014) - Labobar, Mona Fadlianti (Universitas Negeri Semarang, 2018)
This study aimed at investigating the violation of Qualitative maxim, Quantitative maxim, Manner maxim and Relevance maxim. In obtaining the data, the researcher uses the descriptive qualitative to find out the violation of CP in the dialogue among the characters of DBE (2014). The researcher also uses the Documentation method as an Instrument. The Object of this study is the dialogues among the characters of DBE (2014) which violate Grice’s maxims. The result shows that every maxim is violated in the dialogue among the characters of DBE (2014). The writer found the violation of Qualitative maxim with 12 data, the violation of Quantitative maxim with 49 data, the violation of Manner maxim with 18 data and the violation of Relevance/Relation maxim with 26 data. Based on the result of the study, it can be concluded that every maxim of CP is violated by the characters of DBE (2014). The reason of violating the maxims are various and each maxim is violated for some reasons. For example the reason that the speaker violates Qualitative maxim is to cover up the mistake, while the reason that the speaker violates Quantitative maxim is to build up a good social relationship and the speaker violated is manner maxim because provided unclear information. The last is Relevance/Relation maxim. This maxim is violated because the speaker wants to change the topic.